TEACHING TECHNIQUE FOR DEVELOPING READING COMPREHENSION - Fitriadi Lubis (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
The success of teaching reading comprehension depends on various factors, one of them is technique of teaching. There are many techniques that can be applied  in teaching reading comprehension. The most important thing is to select  the most suitable techniques for  reading comprehension, and develop appropriate techniques for that. This is very important for the teachers because a variety of teaching technique can achieve the highest degree of  the students’ learning motivation and teaching result. In this writing, the writer explained the technique of presenting reading comprehension, technique of organizing reading comprehension homework, and technique of reading comprehension evaluation.